Analisa Pengaruh Bauran Pemasaran Jasa Terhadap Keputusan Pengguna OVO Di Kota Manado - Mambu, Evans (Universitas Sam Ratulangi, 2019)
The purpose of this study is to find out and analyze the service mix marketing factors which consist of products, prices, places, promotions, people, physical evidence and processes simultaneously or partially towards ovo user decisions in Manado, this study uses quantitative research methods with research sample of 100 respondents ovo cash users in the city of Manado. The results of this study found that product variables and processes partially had a significant effect on user decisions. While the variables of price, promotion, people and physical evidence partially have no partial effect on ovo user decisions in the city of Manado. As for all variables simultaneously have a significant effect on ovo user decisions in the city of ManadoKeywords: Service Marketing mix,Purchase Decision